THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND STUDENTS ENGLISH ACHIEVEMENTAT X MIA AND IIS OF SMA NEGERI 8 BENGKULU - Novita Sari; Bambang Suwarno; Dedi Sofyan (Universitas Bengkulu, 2018)
The aims of this research were to find out the relationship between students’ emotional intelligence scores and their English achievement scores. This research applied a correlational design. The population consisted of the students’ of SMA Negeri 8 Bengkulu while the sample comprised 70 students’. The data were collected from two instruments, namely, a questionnaire to collect the data on students’ emotional intelligence and a teacher’s score list to collect the data on their English achievement. There was a correlation between students’ emotional intelligence scores and their English achievement scores. However, the coefficient of correlation was 0.261 and it was categorized as ‘low’.